Charge generation mechanism of tandem organic light emitting diodes with pentacene/C70 organic heterojunction as the connecting layer. Issue 2 (14th December 2015) - Guo, Qingxun; Sun, Hengda; Wang, Jiaxiu; Yang, Dezhi; Chen, Jiangshan; Ma, Dongge
Abstract : Charge generation mechanism of a pentacene/C70 planar organic heterojunction is discussed in detail to fabricate high performance tandem OLEDs. Abstract : The working mechanism of a planar organic heterojunction based on pentacene/C70 under reverse voltage is studied through current–voltage ( I – V ) and capacitance–voltage ( C – V ) measurements. It is found that the pentacene/C70 heterojunction generates large amounts of charges and the charge generation is a tunneling process. The proposed Fowler–Nordheim (F–N) model theoretically demonstrates the I – V properties of the pentacene/C70 heterojunction-based device at different temperatures. The heterojunction interface energy diagram is also well determined by ultraviolet photoemission spectroscopy (UPS) measurements, further elucidating this tunneling process. Moreover, by taking advantage of the large charge generation property of the pentacene/C70 heterojunction, a high efficiency green tandem organic light emitting diode (OLED) is successfully fabricated, where not only the current efficiency is doubled, but also the power efficiency is greatly enhanced, proving the excellent performance of the pentacene/C70 heterojunction as charge generation layer (CGL). This work highlights the working mechanism of such heterojunction and provides us a new guide to design high performance tandem OLEDs.